Uncertainty mitigation in online ticketing purchase: The moderating effect of analytics information - So Yeon Han; Younghoon Chang; Siew Fan Wong; Hon Qui Chong; Sangman Lee (International Telecommunications Society (ITS), 2015)
The process of purchasing air tickets is often hovered with much uncertainties. Such uncertainties are introduced by complex pricing strategies and algorithms used by airline companies which vary ticket price based on dates, time of purchase and different routes selected. In order to reduce perceived uncertainties among consumers, agents such as Kayak.com try to present analytics information to assist consumer decision-making. This study seeks to understand the effect of analytics information on consumers' perceived uncertainty and decision to purchase airline tickets. Survey data will be collected from online air ticket buyers. Structural equation modeling technique will be used to analyze the data. Based on the results, we will suggest academic and practical implications.
Keywords: 330; Business Analytics; Uncertainty Mitigation; Online ticket purchase; Trust; Perceived Behavioral Control; Information Quality